Folklore Traditions of Belarusians in the Context of Professional Training of Specialists at the Belarusian State University of Culture and Arts - Alesia I. Gurchenko (Publishing house "Sreda", 2021)
The purpose of the article is to analyze the specifics of training at the Belarusian State University of Culture and Arts, whose professional activities are associated with the embodiment of the traditions of oral folk art in culture and in one of its phenomena - art. In this article, the object of research is the process of training at the Belarusian State University of Culture and Arts. The subject of the research was the filling of the educational process with educational disciplines of folklore, aimed at the formation of social, personal and professional competencies of future specialists in all specialties for which the university is training. Particular attention is paid to the specifics of providing the educational process with such educational disciplines in the areas of specialties and specializations, focused on folklore as a method of translating the folklore traditions of Belarusians in art. The use of methods for analyzing regulatory documents and educational and program documentation made it possible to determine a list of specialties, according to which the process of professional training of students is aimed at translating the authentic traditions of Belarusians into contemporary art. The result of the study showed that in recent decades in Belarusian folklore there is a clear tendency to use by the authors of various methods of understanding the folklore source. It is concluded that the basis of the educational process is made up of competencies, the content of which includes the artistic processing of folklore, at the same time, the educational process does not always aimed at the formation of the necessary knowledge, skills and abilities of interpreting folklore in art.